2021
DOI: 10.14245/ns.2142230.115
|View full text |Cite
|
Sign up to set email alerts
|

Change in Patient-Reported Outcome Measures as Predictors of Revision Lumbar Decompression Procedures

Abstract: Objective: To assess change in Patient-Reported Outcome Measures (PROM) as predictors for revision lumbar decompression (LD).Methods: Patients who underwent primary, single or multilevel LD were retrospectively reviewed. Patients were categorized according to whether or not they underwent revision LD within 2 years of the primary procedure. Visual analogue scale (VAS), Oswestry Disability Index (ODI), 12-item Short Form Health Survey and 12-item Veterans RAND physical component score (SF-12 PCS and VR-12 PCS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In addition, the medical costs associated with secondary surgery were higher than the medical costs of the initial surgery. While many factors are known to be associated with the risk of secondary surgery for DLSD, there are no financial indicators for predicting secondary surgery 33 , 38 , 41 , 49 . In this study, interim costs after initial surgery showed promise in predicting the occurrence of secondary surgery in DLSD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the medical costs associated with secondary surgery were higher than the medical costs of the initial surgery. While many factors are known to be associated with the risk of secondary surgery for DLSD, there are no financial indicators for predicting secondary surgery 33 , 38 , 41 , 49 . In this study, interim costs after initial surgery showed promise in predicting the occurrence of secondary surgery in DLSD.…”
Section: Discussionmentioning
confidence: 99%
“…Our study offers the advantage of a long-term follow-up and a relatively large population; however, due to the de-identified nature of the dataset, we were unable to assess patient-reported outcome measures. To gain insights into factors that mediate the risk of lumbar spine reoperation, it is necessary to conduct a longitudinal prospective study incorporating standardized assessments of pain, low back-related disability, quality of life, and pain medication utilization [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%